2016
DOI: 10.1016/j.copbio.2016.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity and functional capacity in polar soils

Abstract: Global change is disproportionately affecting cold environments (polar and high elevation regions), with potentially negative impacts on microbial diversity and functional processes. In most cold environments the combination of low temperatures, and physical stressors, such as katabatic wind episodes and limited water availability result in biotic systems, which are in trophic terms very simple and primarily driven by microbial communities. Metagenomic approaches have provided key insights on microbial communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 79 publications
2
35
0
1
Order By: Relevance
“…The prokaryotic communities of all samples were dominated by phyla Acidobacteria and Proteobacteria , which was previously observed for other soils of the tundra zone [42,49].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The prokaryotic communities of all samples were dominated by phyla Acidobacteria and Proteobacteria , which was previously observed for other soils of the tundra zone [42,49].…”
Section: Discussionsupporting
confidence: 79%
“…All OTUs belonging to Thaumarchaeota were uncultivable Archaea and were previously observed in other terrestrial environments. Among all Archaeal phyla, Thaumarchaeota are known to be predominate in Arctic and Antarctic soils [49]. We suggest that the relative abundance of Thaumarchaeota , but not their absolute number, decreased from unfixed sands to mature soils because archaeal gene abundances in the unfixed sands were a hundred-fold lower than in the mature soils.…”
Section: Discussionmentioning
confidence: 82%
“…Antarctic terrestrial environments including open soils, permafrost and the surface and interior of rocks, are typically oligotrophic and dominated by psychrophilic and psychrotolerant microbial communities (14). It has been suggested that the extreme abiotic pressures of the environment such as temperature, desiccation stress and UV radiation are dominant drivers of both the diversity and function of cold-adapted bacterial communities in terrestrial polar deserts (5–7).…”
Section: Introductionmentioning
confidence: 99%
“…Just over half of the ribulose-1,5-bisphosphate carboxylase oxygenase (RuBisCO) ( n =79) and phosphoribulokinase ( prk B) ( n =48) genes identified were assigned to Cyanobacteria (Fig. 3), which are the dominant photosynthetic carbon fixers in most desert soils [10, 48, 49], and were relatively common here. The remaining 83 gene assignments belonged to potentially chemosynthetic guilds, including Actinobacteria, Bacteroidetes, Proteobacteria and Planctomycetes (Table S6), which may together serve as important primary producers in soil, and is consistent with the known importance of alternative primary producers in Antarctic soils [50].…”
Section: Resultsmentioning
confidence: 99%
“…In Antarctic soils, the extremely low levels of C and N, consistent with definitions for very low Redfield ratio values substantially constrain microbial growth and activity [7]. Nevertheless, the limited abundance of higher eukaryotes in continental Antarctica soil habitats [8, 9] ensures that the microbial communities are the dominant suppliers of ecosystem services [10]. The extent to which very low Redfield ratios may limit productivity in these systems has not been explored.…”
Section: Introductionmentioning
confidence: 99%